(untitled) (Forum Penelitian Agro Ekonomi, 2022)
The livelihood of the people who live in underdeveloped regions mostly depends on the natural resources-based economy, both in the agricultural, industrial, and other potential resource utilization sectors that have not been managed optimally. The agriculture sector is still the primary source of income for those living in disadvantaged regions. Most farmers have low agricultural knowledge and skills. Facilitating policies and funding are needed to improve the economy in those areas. Another problem is the low quality of human resources, especially farmers and their groups, who are the main drivers of agricultural development in their area. Strengthening the capacity of farmers is also one of the essential policies. The study aims to analyze the capacity building of farmers and farmer groups. The method used in the study is a review of various references. Although government support in funding and facilitation is needed, government support should not create dependence on farmers. Instead, it should make farmers independent. Soft loans with simple procedures are believed to be more educated than providing free input assistance. The government should also prioritize counselling and mentoring to improve the capacity of farmers. Training of trainers for extension workers should be conducted regularly to update knowledge and improve competence, so they can transfer the latest knowledge and skills to farmers. Good knowledge and skills and high capacity can create strong and independent farmers. In turn, they can become productive rural economic actors.